[After]Care : Trauma. Vulnerability. Accountability. - Prugnaud, Véronique; Marcilhacy, Vincent; Dahmani, Taous; Abril, Laia (S.l. : The Eyes, 2022)
Vallejo, Ana ; Afshar, Hoda ; Dostliev, Andrii ; Dostlieva, Lia ; Silvestri, Aida ; Gharbi, Camille ; Danon, Jérémie ; Baker, Hayley Millar ; Carucci, Elinor ; Choumali, Joana ; Tovar, Luis Carlos ; Pinckers, Max ; Suzuki, Mayumi ; Lê, An-My ; Cahana, Kitra ; Shanan, Abdo ; Coombs, Robert Andy ; Newman, Cheryl ; Winant, Carmen ; Masina & Gal ; Yingying, Wang ; Ovcharenko, Margo ; Abril, Laia
boek